The Celtic connection with southern Africa Tracing a genealogy of missionary spirituality - Kritzinger, Johan Jakob 1942- (2014)
It is quite generally accepted that the missionary monks from the Celtic tradition in Ireland and Scotland played a significant role in the Christianisation of Europe during the Dark Ages.This is a story that should not be forgotten. It is also well known that this was preceded by the thorough evangelisation of Ireland and Scotland (and northeast England) itself by these Celtic monks. What is, however, not getting enough attention is the (much later) outreach to southern Africa coming from those same quarters. In this article an effort is made to give credit to this, and to trace the specific spirituality that made all this possible.
Keywords: Andrew Murray; Celtic missionaries; David Livingstone; Lovedale; missionary spirituality; Monastic